(untitled) (Педагогіка вищої та середньої школи, 2010)
In this article the author analyses the effective problems of work with pupils of primary school which are directed on the forming of the spelling habits. She proves the thought that the future teacher has to understand how a strong spelling habit is formed due to coordinating of all components of educational and.